Aphrodisiac Effects of Ethanolic Extract from White Ginger Rhizome (Zingiber officinale Rosc. var. officinarum) on Male Wistar Rats - Oktavia, Swastika; Ernawati, Eneng Elda; Putra, Anca Suryadi (Universitas Pendidikan Ganesha, 2024)
Erectile dysfunction (ED) is a common condition marked by difficulty maintaining a penile erection, often linked to reduced nitric oxide (NO) production. This study investigates the aphrodisiac properties of ethanolic white ginger extract (Z. officinale Rosc. var. officinarum) in male Wistar rats. Sixteen male and sixteen female rats were divided into four groups: two groups received 25% and 50% ginger extract, one served as a negative control, and the other as a positive control using sildenafil. Ginger rhizomes were dried, powdered, and extracted with ethanol. Phytochemical analysis revealed alkaloids, flavonoids, tannins, saponins, and terpenoids. Behavioral parameters, including introduction (approach to females), climbing, and coitus, were observed to evaluate sexual activity. The group treated with 50% ginger extract showed the highest frequency of introduction and climbing, while the sildenafil group exhibited the highest coitus frequency. Statistical analysis using the Kruskal-Wallis test indicated significant differences in sexual behavior across the groups. The study suggests that white ginger extract, especially at higher concentrations, may have aphrodisiac effects by enhancing sexual behavior in male rats. This could be due to its bioactive compounds affecting hormone levels or the nervous system. The findings propose white ginger as a potential natural treatment for ED, with further research required to explore its implications in humans.